Impact of Transcranial Direct Current Stimulation (tDCS) on Neuronal Functions - Das, Suman; Holland, Peter; Frens, Maarten A.; Donchin, Opher (Frontiers in Neuroscience, 2016)
Transcranial direct current stimulation (tDCS), a noninvasive brain stimulation technique, modulates neuronal excitability by the application of a small electrical current. The low cost and ease of the technique has driven interest in potential clinical applications. However, outcomes are highly sensitive to stimulation parameters, leading to difficulty maximizing the technique’s effectiveness. Although reversing the polarity of stimulation often causes opposite effects, this is not always the case. Effective clinical application will require an understanding of how tDCS works; how it modulates a neuron; how it affects the local network; and how it alters inter-network signaling. We have summarized what is known regarding the mechanisms of tDCS from sub-cellular processing to circuit level communication with a particular focus on what can be learned from the polarity specificity of the effects.